The family Hyalidae (Crustacea: Amphipoda: Talitroidea) from Korean waters. 1. Genus Ptilohyale Bousfield & Hendrycks, 2002 - Eun, Ye; Kim, Young-Hyo; Hendrycks, Ed A.; Lee, Kyung-Sook (Zootaxa, 2014)
Two species of the genus Ptilohyale were collected from shallow coastal waters of Korea. One species is identified as a new species: Ptilohyale brevicrus sp. nov. The morphology of gnathopod 2, pereopods, uropods and mandible are the major characteristics which differentiate the new species from its congeners. The remaining species, P. barbicornis (Hiwatari & Kajihara, 1981) is recorded for the first time from Korea. Both species are fully described and illustrated. A key to the family Hyalidae and species of Ptilohyale from Korea is also provided.